2010
DOI: 10.1111/j.1749-7345.2010.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Content Changes of a Tropical Freshwater Fish Labeo rohita Fed Gelatinized and Nongelatinized Starch Diet

Abstract: A 60‐d feeding trial was conducted to study the effect of dietary gelatinized (G) and nongelatinized (NG) starch on deposition of nucleic acid in liver and muscle of Labeo rohita juveniles. Two hundred and thirty‐four juveniles (av. wt. 2.53 ± 0.04 g) were randomly distributed into six triplicate experimental groups. Six semipurified diets containing graded levels of (0, 20, 40, 60, 80, 100) NG and G corn starch, were prepared accordingly: T1 (100% NG, 0% G); T2 (80% NG, 20% G); T3 (60% NG, 40% G); T4 (40% NG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The RNA concentration and RNA/DNA ratios were corroborating to the good growth observed in T32 or T34 group. Similar results of positive relation of RNA/DNA ratio with growth performance was also observed in Labeo rohita (Gangadhar et al, 1997; Kumar et al, 2010). Therefore, results indicate that further increase in protein level is required to achieve maximum growth potential of fish A .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The RNA concentration and RNA/DNA ratios were corroborating to the good growth observed in T32 or T34 group. Similar results of positive relation of RNA/DNA ratio with growth performance was also observed in Labeo rohita (Gangadhar et al, 1997; Kumar et al, 2010). Therefore, results indicate that further increase in protein level is required to achieve maximum growth potential of fish A .…”
Section: Discussionsupporting
confidence: 76%
“…However, subsequently on long‐term exposure the values return to normal by compensatory influx of water as a result of re‐establishment of the extracellular volume (Martínez‐Álvarez et al, 2005; Shahkar et al, 2015). Total protein constitutes of nutritive component that play important role in immune functions (Kumar et al, 2010). In the present study, higher value of serum total protein in the higher protein fed groups suggests the dietary composition or the environmental condition does not influence the immune potential of A .…”
Section: Discussionmentioning
confidence: 99%
“…This study also signifies the common assumption that the protein synthesis is a function of RNA synthesis in the respective muscles. Recently Kumar et al (2010) also reported that dietary supplementation of gelatinized and non-gelatinized starch has changed RNA content of the different tissues of the L. Rohita due to variable fraction of crude protein in the two starch diets. Study also revealed that the gelatinized starch could increase the muscle protein contents as compared to nongelatinized starch which might be attributed to elevated RNA content of the respective muscles.…”
Section: Discussionmentioning
confidence: 99%
“…All dry ingredients weighted carefully, ground and mixed thoroughly and add sufficient amount of water (50 ml) to make it dough mix this mixture for half an hour. Spread this mixture in tray then placed in oven for drying purpose [13]. This material was grounded to make pellets (2 mm).…”
Section: Feed Ingredients and Preparation Of Experimental Dietsmentioning
confidence: 99%